2015
DOI: 10.1111/1346-8138.12754
|View full text |Cite
|
Sign up to set email alerts
|

Variants in SELL,MRPS36P2,TP63,DDB2,CACNA1H,ADAM19,GNAI1,CDH13 and GABRG2 interact to confer risk of acne in Chinese population

Abstract: Acne vulgaris is a common skin disease characterized by chronic inflammation of the pilosebaceous unit resulting from androgen-induced increased sebum production, altered keratinization, inflammation and bacterial colonization of hair follicles by propionibacterium acnes. Our previous genome-wide association study on acne has identified two new susceptibility loci. To search for potential gene-gene interactions and investigate the best-fit association models for the single nucleotide polymorphisms (SNP) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A GWAS study and metaanalysis in a Han Chinese cohort (He et al, 2014) reported suggestive association at two loci (1q24.2 and 11p11) located within the regions of DDB2 and SELL, genes that are implicated in the process of androgen metabolism, inflammation, and scarification. A follow-up of this study (Wang et al, 2015) confirmed the potential involvement of these loci in the pathogenesis of acne. Another GWAS study in European Americans (Zhang et al, 2014) did not detect SNPs with genome-wide association.…”
supporting
confidence: 78%
“…A GWAS study and metaanalysis in a Han Chinese cohort (He et al, 2014) reported suggestive association at two loci (1q24.2 and 11p11) located within the regions of DDB2 and SELL, genes that are implicated in the process of androgen metabolism, inflammation, and scarification. A follow-up of this study (Wang et al, 2015) confirmed the potential involvement of these loci in the pathogenesis of acne. Another GWAS study in European Americans (Zhang et al, 2014) did not detect SNPs with genome-wide association.…”
supporting
confidence: 78%
“…30 It is identified as a novel androgen receptor-interacting protein, mediating contact with AR and the CUL4A-DDB1 complex for AR ubiquitination or degradation. 31 Wang et al 32 performed an in-depth analysis of the GWAS mentioned above and found multiple interactions among 56 SNPs in nine genes, including SELL 9 MRPS36P2 (P adjusted = 4.15 9 10 À10 ), TP63 9 DDB2 (P adjusted = 7.62 9 10 À08 ), DDB2 9 CACNA1H (P adjusted = 1.89 9 10 À07 ) ( Tables 2 and 3). This was interpreted as evidence for different but potentially important roles of these loci in the pathogenesis of acne.…”
Section: Genes and Loci Involved In Acnementioning
confidence: 99%
“…Wang et al . performed an in‐depth analysis of the GWAS mentioned above and found multiple interactions among 56 SNPs in nine genes, including SELL × MRPS36P2 ( P adjusted = 4.15 × 10 −10 ), TP63 × DDB2 ( P adjusted = 7.62 × 10 −08 ), DDB2 × CACNA1H ( P adjusted = 1.89 × 10 −07 ) (Tables and ).…”
Section: Genes and Loci Involved In Acnementioning
confidence: 99%
See 1 more Smart Citation
“…Acne patients have increased sebum secretion, and both acne and activity of the sebaceous glands are under significant genetic control (Bataille et al, 2002;Mourelatos et al, 2007). Recent genome-wide association studies have identified several variants linked to acne susceptibility (He et al, 2014;Navarini et al, 2014;Wang et al, 2015;Zhang et al, 2014).…”
mentioning
confidence: 99%